2002
DOI: 10.1191/1471082x02st032oa
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian spatial models for small area estimation of proportions

Abstract: This article presents a logistic hierarchical model approach for small area prediction of proportions, taking into account both possible spatial and unstructured heterogeneity effects. The posterior distributions of the proportion predictors are obtained via Markov Chain Monte Carlo methods. This automatically takes into account the extra uncertainty associated with the hyperparameters. The procedures are applied to a real data set and comparisons are made under several settings, including a quite general logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
0
9
0
2
Order By: Relevance
“…In this paper, we extend these studies by explicitly incorporating spatial correlation structure in our models. Recent research in epidemiology and geography has demonstrated the importance of explicitly modeling such spatial structure in data (Moura and Migon 2002). We model the spatial correlation by imposing complex dependence structures (i.e., spatially correlated prior distributions) on stock-specific pa-rameters.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we extend these studies by explicitly incorporating spatial correlation structure in our models. Recent research in epidemiology and geography has demonstrated the importance of explicitly modeling such spatial structure in data (Moura and Migon 2002). We model the spatial correlation by imposing complex dependence structures (i.e., spatially correlated prior distributions) on stock-specific pa-rameters.…”
Section: Introductionmentioning
confidence: 99%
“…Another approaches have been proposed to handle the issue of non-sampled area. One of the frequently preferred method is the Spatial EBLUP (see [16][17][18][19][20]). This method utilizes spatial dependencies among regions to derive estimates for sampled areas as well as non-sampled areas.…”
Section: Resultsmentioning
confidence: 99%
“…Penambahan unsur spasial berupa spatial random effect bertujuan untuk mengeksplorasi adanya dependensi spasial yang diharapkan dapat meningkatkan efisiensi hasil estimasi dibandingkan hanya dengan menggunakan random effect yang bersifat saling bebas (independen). Penelitian sebelumnya menggunakan model yang sama untuk estimasi proporsi siswa dengan hasil ujian matematika yang masuk dalam grade rendah di Brasil dimana model dengan unsur spasial lebih baik dibandingkan model tanpa unsur spasial (Moura & Migon, 2002). Penelitian selanjutnya, meggunakan model Poisson Log-normal untuk estimasi jumlah bayi dengan berat kurang dari normal (2.500 gram) pada level distrik di Bangladesh dengan model terbaik adalah model dengan unsur random effect independen dan spasial sekaligus (Alam, Hossain, & Sheela, 2019).…”
Section: Pendahuluanunclassified